Acquisition, spread, and control of Pseudomonas aeruginosa in a cardiothoracic intensive care unit. Issue 10 (October 1982) - Freeman, R; McPeake, P K
Abstract : The isolation rate and spread of infection and colonisation with Pseudomonas aeruginosa in a cardiothoracic intensive care unit was studied over two and a half years. The overall acquisition rate was low (2.68%) and was concentrated in the group of patients undergoing prolonged intensive care (over seven days). Although some cross-infection from long-stay to short-stay patients occurred in 1978 and 1979, when cubicle isolation was inadequate, acquisition of Ps aeruginosa was confined to the long-stay group when isolation facilities became sufficient. Further study of the long-stay patients disclosed two factors--use of broad-spectrum antibiotics and tracheostomy--significantly associated with acquisition of Ps aeruginosa. The possible uses of the results obtained and the particular relevance of a policy of narrow-spectrum chemoprophylaxis for open-heart surgery are discussed.